Adding heat‐treated rapeseed to the diet of yak improves growth performance and tenderness and nutritional quality of the meat. (25th July 2019) - Hao, Lizhuang; Xiang, Yang; Degen, Allan; Huang, Yayu; Niu, Jianzhang; Sun, Lu; Chai, Shatuo; Zhou, Jianwei; Ding, Luming; Long, Ruijun; Liu, Shujie
Abstract: Heat‐treated rapeseed was supplemented to indoor fed yaks in winter to test the effect on dry matter intake (DMI), body mass change, and meat quality. Sixteen 3‐year‐old yak steers (124 ± 15.3 kg) were divided randomly into two groups and were offered either heat‐treated rapeseed (HTR) or rapeseed meal (CONT). The yaks were allowed 14 days for adjustment and measurements were made over 120 d. There was no difference in DMI between groups ( p = 0.67), but average daily gain tended to be higher ( p < 0.056) and feed to gain ratio tended to be lower ( p = 0.050) in HTR than in CONT yaks. Meat from HTR yaks was more tender ( p = 0.006), had higher intramuscular fat ( p = 0.013), and had lower cholesterol content ( p = 0.009) than from CONT yaks. In addition, the atherogenic index was lower (0.37 vs. 0.43; p = 0.049), the PUFA:SFA ratio was higher (0.55 vs. 0.37; p = 0.049), and the n‐6:n‐3 (n‐6 PUFA to n‐3 PUFA) ratio was lower (2.76 vs. 4.78; p = 0.003) in HTR than in CONT yaks, which all favoured the HTR yaks. Meat from HTR yaks met human health standards of a PUFA:SFA ratio of above 0.4 and n‐6:n‐3 ratio of less than 4, whereas meat from CONT yaks just missed these standards.